2005
DOI: 10.1007/11008941_19
|View full text |Cite
|
Sign up to set email alerts
|

Intuitive Human-Robot Interaction Through Active 3D Gaze Tracking

Abstract: One of the biggest obstacles facing humans and robots is the lack of means for natural and meaningful interaction. Robots find it difficult to understand human intentions since our way of communication is different from the way machines exchange their information. Our aim is to remove this barrier by creating systems that react and respond to natural human actions. In this research, we present a robotic system that identifies and picks up an arbitrary object in 3D space that a person is looking at. It is done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…In contrast, Kirchner et al [22] demonstrated how robot gaze can be effective in targeting an individual recipient out of a group of people for a robot initiated handover. Atienza and Zelinksy [1] augmented handover interactions with gaze, demonstrating a system that allowed a human to request an object for handover by looking at it.…”
Section: Gaze In Human-robot Interactionmentioning
confidence: 99%
“…In contrast, Kirchner et al [22] demonstrated how robot gaze can be effective in targeting an individual recipient out of a group of people for a robot initiated handover. Atienza and Zelinksy [1] augmented handover interactions with gaze, demonstrating a system that allowed a human to request an object for handover by looking at it.…”
Section: Gaze In Human-robot Interactionmentioning
confidence: 99%
“…In the system developed by Atienza and Zelinsky [9] the active vision detects when a person is staring at an object and searches the gaze line to find the object of unknown shape and size to be manipulated by a robot arm.…”
Section: Related Literaturementioning
confidence: 99%
“…Other fields would benefit from the intuitive and powerful source of data provided by eye tracking, notably in the fields of robotic control [Jan and Bukhari 2009;Atienza and Zelinsky 2003;Lupu and Ungureanu 2013]and assistive technologies [Frisoli et al 2012;Atienza and Zelinsky 2005]. However, these cannot generally be implemented using a fixed gazing target plane given that their target is often in an uncontrolled environment.…”
Section: Introductionmentioning
confidence: 99%